A GIS Approach: Determinant of Neighbourhood Environment Indices in Influencing Walkability between Two Precincts in Putrajaya. (27th January 2015) - Azmi, Diyanah Inani; Ahmad, Puziah
Abstract: This paper intends to fill the gaps between community facilities planning in the neighbourhood area with walkability using GIS approach to encourage more sustainable environment for all. Several studies have outlined that there are three main neighbourhood environment indices that can contribute towards improving neighbourhood walkability that are (1) residential density; (2) Landuse mixed and (3) street connectivity. The aim of this paper is to determine the neighbourhood environments indices that can influence neighbourhood walkability to reach the community facilities provided in the neighbourhood area. GIS approach was used to utilize neighbourhood environment through layout plan. The significant findings in the paper will show that residential density, street connectivity and non-residents components of mixed land use do affect the neighborhood walkability.